Discovery of the ogre-faced spiders (Aranei: Deinopidae) in Sumatra (Indonesia), with description of a new species - Fomichev, Alexander A.; Omelko, Mikhail M. (Zenodo, 2023)
A new species, Asianopis gorochovi sp. n. is diagnosed and described from the Sumatra Island based on a single male. The family Deinopidae C. L. Koch, 1850 is recorded from Sumatra for the first time. Detailed description, digital photographs and distributional map are provided. The work of Mikhail M. Omelko was carried out within the state assignment of Ministry of Science and Higher Education of the Russian Federation (theme No. 121031000120-9) using equipment of Laboratory of ecology and evolutionary biology of aquatic organisms (Far Eastern Federal University).